Analisis Keandalan Sistem Distribusi 20 KV dari GI Industri Penyulang I.5 Sampai Dengan Gardu Hubung Rapak - Tri Teguh Setiawan; A. Asni B; Bambang Sugeng (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2018)
The reliability of the electric power distribution system can be seen from the SAIDI number (System Average Interruption Duration Index) or long extinguished in one period and SAIFI (Sytem Average Interruption Frequency Index) or outages in one period. PT PLN (Persero) Balikpapan Area is currently trying to improve service used reliability improvement methods, namely by maneuvering the radial system network load into a loop system network and installing reclosers. Penyulang Industri 5 (I.5) for 2017 has SAIDI realization value of 7.741 hours / year, and SAIFI is 5.03 times / year. It can be interpreted that SAIDI-SAIFI 5 industrial feeders are relatively few of the value of the revised targets. This shows that industrial feeder 5 has a high level of reliability. But it still does not meet the IEEE Std standard. 1366-2000 with a SAIDI score of 2.30 hours / year and a SAIFI value of 1.45 times / year. After the improvement is obtained the value of SAIDI is almost close to the IEEE Std standard value. 1366-2000 which is 2,365 hours / year.Keywords : Reliability, SAIDI/SAIFI, Load Manuver, Recloser.